Input Versus Output Taxation in an Experimental International Economy - Arno Riedl; Frans van Winden (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper is concerned with a policy oriented macroeconomic experiment involving an international' economy with a relatively small home' country and a large foreign' country. It compares the economic performance of two alternative tax systems as a means to finance unemployment benefits: a sales-tax-cum-labor-subsidy system versus a wage tax system. The two systems are applied to the home country, while the wage tax system always obtains in the foreign country. In stark contrast with expectations of experts the sales tax system clearly outperforms the wage tax system, using standard economic indicators. It is argued that producers' reluctance to incur costs up-front while being uncertain about product prices can explain this outcome. Several pieces of evidence are provided to support this claim. The results strongly suggest that behavioral aspects have to be taken into account also in applied macroeconomic models.
Keywords: 330; laboratory experiment; wage tax; sales tax; macroeconomic policy; behavioral economics